2001
DOI: 10.1002/j.0022-0337.2001.65.8.tb03422.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Specific Dental School‐Taught Restorative Techniques by Practicing Clinicians

Abstract: In 1995, a survey requesting information about the utilization of certain prosthodontic techniques was mailed to 3,544 graduates of a midwestern dental school. Responses were received from 1,455 alumni, representing a 41 percent return rate. In general, the results are consistent with international and national trends and show significant disparity in the utilization rates of certain procedures between general dentists and prosthodontists, as well as a disconnect between what is taught in the undergraduate den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 4 publications
0
11
1
1
Order By: Relevance
“…Recent literature has questioned the real need for conventional methods . Reports of adopted practices for denture fabrication have revealed that dentists in private practice do not employ traditional sequences of procedures; instead, they employ simpler methods.…”
mentioning
confidence: 99%
“…Recent literature has questioned the real need for conventional methods . Reports of adopted practices for denture fabrication have revealed that dentists in private practice do not employ traditional sequences of procedures; instead, they employ simpler methods.…”
mentioning
confidence: 99%
“…The traditional academic method (T) of fabrication of conventional dentures taught in most North American dental schools 10,11 is not used by most general practitioners in the United States 12 and United Kingdom 13 . They use simplified methods(S), and this has caused concern within the dental education community 13 .…”
mentioning
confidence: 99%
“…The use of custom trays is regarded as the gold standard and is adopted by the majority of prosthodontic specialists. 16 A custom tray ensures constant material thickness and facilitates a dental and/or mucosal support. A variety of in vitro studies demonstrate that a uniform spacer thickness not exceeding 2 mm offers ideal preconditions for accurate impressions in terms of dimensional accuracy and marginal precision.…”
Section: Discussionmentioning
confidence: 99%
“… 15 More recent data reveals a significant disparity in the utilization rate of custom trays between general dentists (68%) and prosthodontic specialists (100%). 16 …”
Section: Introductionmentioning
confidence: 99%